2021
DOI: 10.3758/s13423-021-01904-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting as a learning strategy

Abstract: This article attempts to delineate the procedural and mechanistic characteristics of predicting as a learning strategy. While asking students to generate a prediction before presenting the correct answer has long been a popular learning strategy, the exact mechanisms by which it improves learning are only beginning to be unraveled. Moreover, predicting shares many features with other retrieval-based learning strategies (e.g., practice testing, pretesting, guessing), which begs the question of whether there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 59 publications
2
43
0
Order By: Relevance
“…The evidence for the error-correction hypothesis in this pretesting paradigm is not compelling. However, it has been argued that having confidence in one's response is necessary to observe surprise-based prediction errors and the subsequent beneficial effects on learning (Brod, 2021). Thus, the error-correction theory may well find support in paradigms that require participants to make informed predictions (e.g., answering familiar trivia questions) rather than guesses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence for the error-correction hypothesis in this pretesting paradigm is not compelling. However, it has been argued that having confidence in one's response is necessary to observe surprise-based prediction errors and the subsequent beneficial effects on learning (Brod, 2021). Thus, the error-correction theory may well find support in paradigms that require participants to make informed predictions (e.g., answering familiar trivia questions) rather than guesses.…”
Section: Discussionmentioning
confidence: 99%
“…In the pretesting paradigm, participants may not have much confidence in their guesses, and therefore may not be surprised to learn that their guesses were wrong. This low level of confidence and surprise may reduce the likelihood of an error-correction mechanism being triggered, especially when compared to other paradigms in which the participants generate informed predictions (see Brod, 2021). Indeed, the participants may even be more surprised if they generate a guess that is close to the true answer in the pretesting paradigm (i.e., the perception of a near miss).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The encoding setup of Experiments 2A and 2B minimized the need for explicit prediction by requiring a categorization (rather than a prediction) task. Indeed, recent findings on the effect of PE on pupil dilation and in relation to memory have showed that explicitly requiring a predictive response at encoding can be crucial to measure predictionrelated effects on memory performance (Brod et al, 2018;Brod, 2021a). The lack of a PEmediated effect on episodic memory in the absence of an explicit prediction task challenges the automaticity of the predictive processing mode, particularly concerning its long-term memory consequences.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate on this distinction based on the similarities between our encoding tasks and those in Brod et al (see also, (Brod, 2021b;Simonsmeier et al, 2021)). More specifically, with almost identical setups, prediction and post-diction mainly differ by the fact that prediction prompts the pre-activation of a representation that can be contrasted directly against the incoming stimulus while post-diction does not (since this contrasting can only happen after the stimulus onset; (Brod, 2021a)). In other words, the pre-activation of a specific representation based on prior knowledge or memory is the necessary condition for PE to arise.…”
Section: Predictions and Predictive Effects On Memory: Automatic Or Task Dependent?mentioning
confidence: 99%